Manajemen strategi dan risiko sebagai pilar penguatan lembaga keuangan syariah di era global - Fatkhunnaja, Achmad Iqbal (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the role of strategic management and risk management in strengthening the competitiveness and resilience of Islamic financial institutions globally. This study employed a descriptive qualitative method with a library research approach through a review of seven relevant scientific articles. The results indicate that implementing risk management aligned with Islamic principles can increase institutional resilience to global economic turmoil. The use of SWOT analysis has proven effective in formulating competitive strategies based on internal strengths and external opportunities. Meanwhile, digital transformation is a crucial instrument for improving operational efficiency and customer satisfaction while remaining guided by Islamic values. International expansion, on the other hand, demands strengthened governance, product innovation, and adjustments to cross-border policies. Overall, the collaboration between risk management, business strategy, and digitalization is a key factor in maintaining the sustainability and competitiveness of Islamic financial institutions globally.